Risk Factors for the Occurrence of Erosive Esophageal in Patients with Dyspepsia - Katharina Setyawati; Murdani Abdullah; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2010)
Background: The prevalence of erosive esophagitis tends to increase recently. It induces higher medical expense, loss of working time, and decreases quality of life. However the study on risk factors of erosive esophagitis scarcely reported in Indonesia. This study aimed to find the association between age, sex, smoking, alcohol drinking, body mass index, hiatal hernia, the use of non steroidal anti-inflammatory drugs (NSAID), and drugs that decrease lower esophageal sphincter (LES) tone with the occurrence of erosive esophagitis in dyspeptic patients. Method: A case-control study was conducted on patients with dyspepsia who underwent upper gastrointestinal endoscopy procedure and had been interviewed to determine risk factors for erosive esophagitis in July - September 2008. The association between risk factors and the occurrence of erosive esophagitis were analyzed using Chi-square, which subsequently revealed p 0.25, this variable included in multivariate analysis. Result: There were 135 patients fulfilled criteria; 45 patients as cases and 90 patients as controls. The association was found between the occurrence of erosive esophagitis in dyspeptic patients and smoking more than 15 cigarette/day (OR 15.43; p = 0.00; CI 95% 4.77-49.88), the use of NSAID (OR 9.49; p = 0.00; CI 95% 2.77-32.53) and the consumption of drugs that decrease LES tone (OR 3.56; p = 0.02; CI 95% 1.26-10.02). Conclusion: Smoking more than 15 cigarettes/day, use of NSAID and drugs that decrease LES tone is a risk factors for the occurrence of erosive esophagitis. Keywords: erosive esophagitis, NSAID, smoking, drugs that decrease LES tone